Lexical-Functional Grammar of the Croatian Language - Seljan, Sanja (Array, 1999)
Lexical Functional Grammar (LFG) is relatively new type of grammar, developed 1982. by Kaplan & Bresnan as one of the Unification Grammars. LFG has been used for text analy-sis, machine translation and text generation. LFG is formal non-Transformational Grammar that has been applied to all types of languages (English, French, Italian, German, Arabic, Russian, some African languages, etc.). This article aims to prove the justified interest for LFG, being based on several hypothesis: 1) LFG grammar unifies the knowledge from informatics, linguistics and mathematics and thus has the informatic application. 2) Although it uses linguistic knowledge, it is necessary to do some modifications from the traditional grammar. 3) As this grammar tends to be universal, application of LFG on the Croatian language and its peculiarities would be one more test for this formal grammar.